Motor Competence and Body Composition in young adults: An exploratory study. (June 2019) - Silva, Bruno; Rodrigues, Luís Paulo; Clemente, Filipe Manuel; Bezerra, Pedro; Cancela-Carral, José Maria
Abstract: Background: The association between obesity and physical inactivity strongly and independently predict overall obesity in young adulthood. Physical inactivity and increasing obesity in our society is multifaceted, but on key factor to promote physical activity is motor competence (MC). Purpose: This study aimed to analyse a physically active group of young adults by investigating the correlations between MC, adiposity and body mineral density by using dual X-ray absorptiometry (DXA). Methods: Forty-four young men (22, 1 ± years; 69, 0 ± kg; 173, 7 ± meters) and 21 young women (20, 2 ± years; 63, 8 ± kg; 169, 6 ± meters) participated in this study and completed anthropometrics; DXA; Motor Competence assessment battery that comprise two tests for each of the three constructs: locomotor, manipulative and stability. Descriptive statistics were considered and Spearman's correlation test to examine the association between MC scores and DXA results. The Mann-Whitney test was used to compare males to females for p < 0, 05. Results: Motor Competence (MC) variables and body composition in female revealed significant associations only between shuttle run and total fat (r = −0, 648). In males, demonstrate several positive statistically associations with MC Stability and Locomotor tasks and constructs (p < 0, 05). Conclusions: In very active young adults, MC positive influences weight status, particularly in locomotor and stability tasks.